Cycloart-24-ene-3 beta,26-diol from the leaves of Aglaia exima - Awang, K.; Loong, X.M.; Mohamad, K.; Chong, S.L.; Ng, S.W. (International Union of Crystallography, 2010)
Cycloart-24-ene-3 beta,26-diol, C(30)H(50)O(2), isolated from the leaves of Aglaia exima, has three six-membered rings fused together that adopt chair conformations. There are two independent molecules in the asymmetric unit. O-H...O hydrogen bond interactions between the hydroxyl groups in the 3 beta and 26 positions lead to the formation of a layer structure parallel to (102)